Effect of Ultrasound Combined With Microbubble Therapy on Interstitial Fluid Pressure and VX2 Tumor Structure in Rabbit - Zhang, Qianyun; Jin, Hai; Chen, Liping; Chen, Qiaoli; He, Yan; Yang, Yuwen; Ma, Suihong; Xiao, Shuyi; Xi, Fen; Luo, Qiong; Liu, Jianhua (Frontiers in Pharmacology, 2019)
Interstitial fluid pressure (IFP) in tumor tissue was significantly higher than normal tissue, which reduced the effective of therapeutic drugs. There are many methods to decrease the IFP level, such as normalizing blood vessel, decreasing the content of hyaluronic acid and collagen fibers in extracellular matrix (ECM), and recovering lymphatic function. Reducing tumor IFP may become a new way in cancer therapy. Our research aimed to focus on the relationship and mechanism between ultrasound combined with microbubble therapy and IFP. The VX2 tumor in rabbit was treated with ultrasound combined with microbubbles in different intensity. The IFP was measured by WIN method. The collagen fibers and reticular fibers were stained by Masson and Gordon-Sweets respectively. The results show that low-frequency NFU combined with microbubbles therapy influence the IFP in tumor tissues, low-frequency NFU with low pressure increased the IFP while middle-high pressure decreased the IFP. The results shown the structure and content of collagen fibers and reticular fibers in tumor tissue were rarely influenced by the treatment. Our research pointed out a new way to promote the effective of reduce IFP anti-tumor therapy.